Membangun Generasi Muda Unggul melalui Kewirausahaan di SMK St. Fransiskus 1 Jakarta - Yusuf Suhardi; Arya Darmawan; Meita Pragiwani; Zulkarnaini Zulkarnaini; Sri Handoko Sakti (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
This Community Service activity aims to motivate vocational school graduates to pursue business ventures and equip them with techniques for starting their own businesses. It offers alternative pathways for graduates beyond continuing education or entering the workforce, providing them with tools to build businesses from scratch. This motivational approach serves as a strong driver, highlighting the vast opportunities available in entrepreneurship. The program utilizes methods such as lectures, discussions, Q&A sessions, and business simulations. Participants are exposed to real-life case studies of both successful and failed businesses, along with strategies for overcoming challenges and achieving entrepreneurial success. This approach is particularly engaging, as it emphasizes the potential for unlimited income in business. The activity was conducted on Friday, July 12, 2024, at the SMK St. Fransiskus 1 Jakarta. The counseling session concluded with positive outcomes, as participants demonstrated an enhanced understanding and a strong desire to engage in business creativity and develop entrepreneurial ideas. This was evidenced by questionnaire responses showing a high entrepreneurial spirit. Participants expressed readiness to implement business plans and integrate entrepreneurship lessons from school, with ongoing guidance from teachers and school programs to support their efforts.